Penetapan Status Mutu Air Situ Jatijajar dan Situ Gadog Kota Depok, Jawa Barat Menggunakan Indeks Pencemar - Denis Ergi Septyan Permana; Diana Irvindiaty Hendrawan; Melati Ferianita Fachrul (Universitas Trisakti, 2021)
The purpose of this research is to determine the potential activities that cause pollution in Situ Jatijajar and Situ Gadog, analyze the water quality and the status of water quality Situ Jatijajar and Situ Gadog. This study uses secondary data on water quality from Situ Jatijajar and Situ Gadog in Depok City, West Java year 2017-2019 from the Environment and Sanitation Office of Depok City. 10 parameters were analysis, pH, COD, BOD, DO, Phosphate, Nitrate, Fecal Coliform, Total Coliform, fatty oil, and detergent. Situ Jatijajar water quality in 2017-2019, pH ranges from 7.16, -7.33, BOD 7.33-9.43 mg/L, COD 15.4-21.1 mg/L, DO 2.44-5.25 mg/L, Phosphate 0.18-0.0043 mg/L, Nitrate 3.02-0.37 mg/L, Fecal Coliform 1600-9200 MPN/100 mL, Total Coliform 160.000-35.000 MPN/100 mL, Fatty Oil 200-300 mg/L and Detergent 45.4-20.7 mg/L. The results of measuring the quality of Situ Gadog water in 2017-2019 for pH parameters 9.55-7.24, BOD 4.29-5.36 mg/L, COD 10.3-12.41 mg/L, DO 3.50 -4.55 mg/L, Phosphate 0.064-0.0055 mg/L, Nitrate 2.76-0.37 mg/L, Fecal Coliform 2200-2400 MPN/100 mL, Total Coliform 2,080-5,400 MPN/100 mL, Fatty Oil 100-400 mg/L and Detergent 35.7-44 mg/L. The water quality status of Situ Jatijajar in 2017 was 6.197, in 2018 was 3.290 and 2019 was 4.312. The water quality status of Situ Gadog in 2017 was 2.618, in 2018 was 1.646 and 2019 was 2.161. The water quality status of Situ Jatijajar and Situ Gadof is classified as lightly polluted.